2021
DOI: 10.22159/ajpcr.2021.v14i10.42431
|View full text |Cite
|
Sign up to set email alerts
|

Role of Combination Drug Therapy for Management of Hypertension With Increasing Age

Abstract: Objective: In South Asia, hypertension is the third highest factor contributing in public health burden of disease and major risk factor for coronary artery disease especially in women and old age people. The study was aimed to determine the role of gender and age (20–80 years) on severity of hypertension to design an effective schedule for management of hypertension. Methods: The levels of serum cholesterol, triglycerides (TG), high-density lipoprotein (HDL), low-density lipoproteins (LDL), and blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Other drugs in the angiotensin II receptor blocker (ARB) family, which also includes olmesartan, include telmisartan, candesartan, losartan, valsartan, as well as irbesartan [5]. ARBs specifically bind to the angiotensin receptor 1 (AT1), blocking the binding of the protein angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…Other drugs in the angiotensin II receptor blocker (ARB) family, which also includes olmesartan, include telmisartan, candesartan, losartan, valsartan, as well as irbesartan [5]. ARBs specifically bind to the angiotensin receptor 1 (AT1), blocking the binding of the protein angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of the renin-angiotensin system with ACE inhibitors has provided effective treatment of these conditions; however, some of the adverse effects of ACE inhibitors appear to be unrelated to angiotensin II blockade. For example, cough and angioedema are due to other effects of ACE inhibition, such as the degradation of bradykinins and prostaglandins [7]. In general, ARBs are well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…A hypertension management schedule involving (BP)/Cholesterollowering drugs and lifestyle changes for a period of 60 d showed that combination drug therapy was more effective than immunotherapies of the same drugs used at higher dosages [9]. Various types of fixeddose combinations have recently been developed and used, revealing improved patient adherence to their convenient regimen [6].…”
Section: Introductionmentioning
confidence: 99%